Occupational Category and Professional Title Influencing the Knowledge, Attitudes and Practice (KAP) of Quality Training: A Cross-Sectional Survey From a Tertiary General Hospital - Ling-Feng Zhu MB; Xi-Feng Wang MSc; Hai-Xiao Chen PhD; Qiao Liu MSc; Lin-Hong Zhu MSc; Qian-Shan Ying MB (SAGE Publishing, 2024)
Quality improvement is an international priority, and quality education and training are important parts of hospital quality management. The aim of this study was to understand the knowledge, attitudes and practices (KAP) and its influencing factors related to quality training in medical staff. A questionnaire survey was conducted by convenience sampling to assess the KAP of quality training in Taizhou Enze Medical Center. Principal component analysis was used to extract factors from the questionnaire. Descriptive statistics (frequency, median, mean), Kendall grade correlation analysis, and Mann-Whitney U tests were used to analyze the data. A total of 205 staff members participated in the questionnaire survey. For the 5 factors of the KAP scale, the highest score was factor F4, recognition and support for quality training (mean = 90.55, median = 100), followed by factor F3, perceived benefits (mean = 84.46, median = 85.65). Relatively lower scores were found for factor F2, quality knowledge learning and mastery (mean = 63.09, median = 63.89), and F5, quality management practices and sharing (mean = 82.07, median = 75.00). There was a correlation between the 5 factors. The scores of F2 (quality knowledge learning and mastery) for staff with senior professional titles were higher than those for staff with intermediate professional titles or below. The score of F3 (perceived benefits of quality training) in medical technicians and nurses was higher than in doctors and administrative personnel. Our findings showed that the respondents' attitude toward quality training was positive, but their knowledge mastery and practice behaviors should be further improved. Occupational category and professional title were the influencing factors of the quality training KAP. Therefore, hospital should conduct quality management training at a wider scope according to the competency requirements of different groups, and further optimize the improvement and innovation system.